Cash flow news, discount rate news, and momentum - Celiker, Umut; Kayacetin, Nuri Volkan; Kumar, Raman; Sonaer, Gokhan (Journal of Banking & Finance, 2016)
We examine the effect of aggregate cash flow news and discount rate news on momentum returns. We find that momentum profits are higher following aggregate positive cash flow news, even in down markets or low sentiment periods. This finding expands on the evidence in Cooper et al. (2004) that momentum is significant only when past market returns are non-negative and in Antoniou et al. (2013) that momentum is weaker when sentiment is pessimistic. We find that the higher momentum profits during aggregate positive cash flow news periods are primarily driven by the losers continuing to underperform in subsequent periods. Our findings are consistent with the Hong and Stein (1999) model in the sense that gradual diffusion of contradictory news is accentuated when change in wealth is positive and relatively more permanent.